Pulmonary Embolism Testing Among Emergency Department Patients Who Are Pulmonary Embolism Rule‐out Criteria Negative. (19th September 2017) - Buchanan, Ian; Teeples, Troy; Carlson, Margaret; Steenblik, Jacob; Bledsoe, Joseph; Madsen, Troy
Abstract: Objective: Previous studies have demonstrated that rates of pulmonary embolism (PE) testing have increased without a concomitant decrease in PE‐related mortality. The Pulmonary Embolism Rule‐out Criteria (PERC) intend to reduce testing for PE in the emergency department (ED) by identifying low‐risk patients ("PERC‐negative") who do not require D‐dimer, computed tomography pulmonary angiogram (CTPA), or ventilation/perfusion (VQ) scan for PE. This study assesses PE testing rates among PERC‐negative patients presenting to an urban academic ED. Methods: We prospectively enrolled a convenience sample of ED patients with chest pain and/or shortness of breath presenting between June 2010 and December 2015. We recorded baseline variables at the time of ED presentation, information on testing performed in the ED, and the diagnosis of acute PE during the ED visit. We classified patients as PERC‐positive or PERC‐negative utilizing baseline variables and clinical characteristics. Results: Of the 3, 024 study patients, 54.8% (95% confidence interval = 53%–56.5%) were female and the mean age was 51.7 (51.1–52.3) years. A total of 17.5% (16.2%–18.9%) of study patients were PERC‐negative and 33.7% (32%–35.4%) of all patients underwent testing for PE. A total of 25.5% (22%–29.4%) of PERC‐negative patients had PE testing compared to 35.4% (33.6%–37.3%) of PERC‐positive patients (p < 0.001). A total of 7.2% (5.3%–9.7%) of PERC‐negative patients had advanced imaging without a D‐dimer compared to 19.2% (17.8%–20.8%) of PERC‐positive patients (p < 0.001). In multivariate analysis, factors associated with PE testing in PERC‐negative patients included age, white non‐Hispanic race/ethnicity, pleuritic chest pain, and a complaint of both chest pain and shortness of breath. Two PERC‐negative patients (0.4%) were diagnosed with an acute PE in the ED compared to 2.2% of PERC‐positive patients (p = 0.008). The overall testing yield for PE was 1.6% (0.4%–9.2%) among PERC‐negative patients versus 6.3% (4.9%–8.1%) among PERC‐positive patients (p = 0.017). Conclusion: In an academic ED, a significant proportion of PERC‐negative patients underwent testing for PE, including CT or VQ scan without D‐dimer risk stratification. Future areas of research may include evaluating factors that lead clinicians to pursue PE testing in PERC‐negative patients and implementing clinical pathways to minimize practice variability among these patients.